The Role of Stakeholders in Preventive Effort Agains Early Marriage - Desy Dwi Cahyani; Gita Kostania (An Idea Nursing Journal, 2026)
Background: Early marriage continues to pose significant public health and social challenges in Indonesia, contributing to domestic violence, divorce, poverty, school dropout, and high-risk pregnancies among adolescents. Objective: This study explored the roles of stakeholders in preventing early marriage across seven villages in Pare District, Kediri Regency Methods: utilizing a descriptive qualitative design. Participants included village heads, village officials, village midwives, heads of public health centers, and religious leaders. Data were collected through Focus Group Discussions (FGDs) and analyzed using data reduction, data display, conclusion drawing, and verification. Results: The results indicate that effective prevention of early marriage requires cross- sector collaboration, educational interventions, and structured policy implementation. Key stakeholders, such as village governments, health cadres, community leaders, and educational institutions, contribute through educational and socialization initiatives, including youth-integrated health posts, youth organizations, and school-based counseling. While stakeholder collaboration has demonstrated effectiveness, persistent challenges include limited public awareness, inadequate intersectoral coordination, and uneven program distribution Conclusion:Education emerged as a strategic element, with schools supporting prevention efforts through formal instruction, extracurricular activities, and promotion of legal awareness. Strengthening program evaluation by using measurable, data-driven indicators is recommended.